Peran Keluarga Besar Dalam Mencegah Pelanggaran Hak Anak oleh Ibu Saat Pembelajaran Daring Dusun Kemantren Desa Terusan Kabupaten Mojokerto - Wardhana, Fajar Tri (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the role of extended family in preventing violations of children’s rights and the forms of violations of children’s rights that occur during online learning. The theoretical basis used is the role theory of Biddle and Thomas with several indicators, namely expectations (Expectation), norms (Norm), forms of behavior (Performance) and sanctions (Sanction). This research uses a qualitative approach with a descriptive design. This research was conducted in Kemantren Hamlet, Terusan Village, Mojokerto Regency, in 9 families who have children still in elementary school. Data were collected through interviews, observations and documentation and then analyzed using data reduction techniques, data presentation and conclusion drawing. The results of this study indicate that the role of the extended family in preventing violations of children’s rights by mothers during online learning in Kemantren Hamlet, Terusan Village is (1) a provider of social support for the family, providing opportunities for mothers to increase their capacity and always try to fulfill their responsibilities in fulfilling children’s rights with the help of other family members’ interventions, (2) a provider of pleasure, calmness to grandchildren even though only accompanying learning, defending and comforting when their grandchildren cry, (3) a source of wisdom, following parental rules by supervising and giving advice on inappropriate behavior of parents and grandchildren.